Tuning the Resonance of the Excessively Tilted LPFG-Assisted Surface Plasmon Polaritons: Optimum Design Rules for Ultrasensitive Refractometric Sensor - Zhihong Li; Jie Shen; Qiuping Ji; Yaoju Zhang; Xiukai Ruan; Yuxing Dai; Zhennao Cai (IEEE Photonics Journal)
An excessively tilted LPFG-assisted surface plasmon polaritons sensor (Ex-TLPFG assisted SPP sensor) with ultrahigh sensitivity is proposed and numerically investigated using the finite-element-method-based full-vector complex coupled mode theory. We show that the SPP mode is transited (or excited) gradually from both the p-polarized TM $_{0,j}$ and EH $_{v,j}$ ( $v\geq 1$ ) modes, and hence, the proposed SPP sensor can be tuned to achieve strong resonance of either the degenerate TM $_{0,j}$ and EH $_{2,j}$ modes or EH $_{1,j}$ mode to optimize the sensitivity for analyte refractive index sensing. The results confirm that a transition point corresponding to the phase matching curve of the SPP mode is obtained, which can be used to predict the optimized grating period. By this approach, ultrasensitive SPP refractometric sensor can be obtained and the sensitivity can be further improved through a simple method: reducing the fiber cladding combined with an optimized grating period. We demonstrate that a giant sensitivity as high as $10100\,\text{nm}/\text{RIU}$ is achieved for the degenerate TM $_{0,32}$ and EH $_{2,32}$ modes (or $7400\,\text{nm/RIU}$ for the EH $_{1,32}$ mode). These appealing characteristics make the proposed Ex-TLPFG-assisted SPP sensor ideal for biochemical analyte sensing applications.